Organizational Factors and Employees Commitment - Okyere-Kwakye, Eugene; Otibu, Ferdinand (Advances in Social Sciences Research Journal, 2016)
For an organization to survive in this century, leaders of the organization must offer a greater sense of meaning and purpose for their employees to enjoy working in the organization. In today’s highly competitive environment, employees don’t only look up for increment in pay to be committed but issues such as good leadership style, well structured organizational culture and other factors also have an influence on their level of commitment. Based on previous studies, the researchers develop a conceptual framework to suggest a relationship between organizational commitment and five organizational factors i.e., organizational culture, organizational structure, leadership style and rewards as the constructs. Questionnaire is proposed to be used as a data collection tool and multiple regressions as the statistical technique that would be used to analyze the data.